2017
DOI: 10.1111/cea.12923
|View full text |Cite
|
Sign up to set email alerts
|

The practice and perception of precautionary allergen labelling by the Australasian food manufacturing industry

Abstract: Currently, we estimate that at least 30% of products may have been through a risk assessment process and yet bear no PAL statement on the label. Permissive labelling could be incorporated onto these products if they have been assessed to be safe for consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This will help patients to ask the right questions and help industry, healthcare professionals and retailers to answer them in the right way, and with confidence. We can learn from the experience in Australia with the take up of VITAL 2.0™ . When expectations were raised among consumers, industry felt that these expectations should be met.…”
Section: Applying the New Ifaam Approach To Precautionary Allergen Lamentioning
confidence: 99%
See 1 more Smart Citation
“…This will help patients to ask the right questions and help industry, healthcare professionals and retailers to answer them in the right way, and with confidence. We can learn from the experience in Australia with the take up of VITAL 2.0™ . When expectations were raised among consumers, industry felt that these expectations should be met.…”
Section: Applying the New Ifaam Approach To Precautionary Allergen Lamentioning
confidence: 99%
“…We can learn from the experience in Australia with the take up of VITAL 2.0™. 36,37,59 When expectations were raised among consumers, industry felt that these expectations should be met. The widest acceptance across stakeholders would be achieved when the use of when and how to apply PAL is regulated by law.…”
Section: How Can Healthcare Professionals Better Help Patients To Umentioning
confidence: 99%
“…172 A total of 59 manufacturers completed the questionnaire. 172 A total of 59 manufacturers completed the questionnaire.…”
Section: Precautionary Allergen Labellingmentioning
confidence: 99%
“…Zurzolo and colleagues have looked at how widely the Australian food industry is using the VITAL approach to making rational decisions on precautionary allergen labelling. 172 A total of 59 manufacturers completed the questionnaire. They reported that a quarter of products had been through the VITAL risk assessment process but had no PAL statement on the label.…”
Section: Precautionary Allergen Labellingmentioning
confidence: 99%
“…Within this evidence‐based approach would mean that only products likely to cause a reaction would have a precautionary allergen label . This would deliver certainty for consumers with allergies and help healthcare professionals give better advice …”
mentioning
confidence: 99%